Bitter melon juice-intake modulates glucose metabolism and lactate efflux in tumors in its efficacy against pancreatic cancer. (13th June 2019) - Dhar, Deepanshi; Raina, Komal; Kant, Rama; Wempe, Michael F; Serkova, Natalie J; Agarwal, Chapla; Agarwal, Rajesh
Abstract: The established role of bitter melon juice (BMJ), a natural product, in activating master metabolic regulator adenosine monophosphate-activated protein kinase in pancreatic cancer (PanC) cells served as a basis for pursuing deeper investigation into the underlying metabolic alterations leading to BMJ efficacy in PanC. We investigated the comparative metabolic profiles of PanC cells with differential KRAS mutational status on BMJ exposure. Specifically, we employed nuclear magnetic resonance (NMR) metabolomics and in vivo imaging platforms to understand the relevance of altered metabolism in PanC management by BMJ. Multinuclear NMR metabolomics was performed, as a function of time, post-BMJ treatment followed by partial least square discriminant analysis assessments on the quantitative metabolic data sets to visualize the treatment group clustering; altered glucose uptake, lactate export and energy state were identified as the key components responsible for cell death induction. We next employed PANC1 xenograft model for assessing in vivo BMJ efficacy against PanC. Positron emission tomography ([ 18 FDG]-PET) and magnetic resonance imaging on PANC1 tumor-bearing animals reiterated the in vitro results, with BMJ-associated significant changes in tumor volumes, tumor cellularity and glucose uptake. Additional studies in BMJ-treated PanC cells and xenografts displayed a strong decrease in the expression of glucose and lactate transporters GLUT1 and MCT4, respectively, supporting their role in metabolic changes by BMJ. Collectively, these results highlight BMJ-induced modification in PanC metabolomics phenotype and establish primarily lactate efflux and glucose metabolism, specifically GLUT1 and MCT4 transporters, as the potential metabolic targets underlying BMJ efficacy in PanC.